2012
DOI: 10.1155/2012/267595
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto’s Thyroiditis and Kikuchi’s Disease: Presentation of a Case and Review of the Literature

Abstract: We report the case of a 19-year-old woman with a history of Hashimoto's thyroiditis who presented with tender right anterior cervical lymphadenopathy and fever. Workup for infectious, autoimmune, and malignant causes was unremarkable. Surgical removal of cervical lymph nodes after detailed magnetic resonance (MR) imaging disclosed necrotizing lymphadenitis, also known as Kikuchi's disease (KD). The patient was treated with a short-term course of steroids, due to the onset of pancytopenia and borderline antipho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Awareness of this disorder will help to prevent misdiagnosis and inappropriate treatment as it is strongly associated with autoimmune disorders like hashimoto's thyroiditis or systemic lupus erythematous (SLE) and mimic lymphoma, TB etc. 4…”
Section: Professor and Head Ent-hns Anwer Khanmentioning
confidence: 99%
“…Awareness of this disorder will help to prevent misdiagnosis and inappropriate treatment as it is strongly associated with autoimmune disorders like hashimoto's thyroiditis or systemic lupus erythematous (SLE) and mimic lymphoma, TB etc. 4…”
Section: Professor and Head Ent-hns Anwer Khanmentioning
confidence: 99%
“…Recently, Kang et al [ 7 ] reported that of 86 children and adolescents who were diagnosed with KFD, 2 were also found to be afflicted with thyroiditis. However, there have been few reports about the potential relationship between Hashimoto thyroiditis with KFD [ 8 , 9 ]. Therefore, we report a case of Hashimoto thyroiditis in a girl with a history of KFD.…”
Section: Introductionmentioning
confidence: 99%
“…Further evaluation of these relationships, however, is necessary. To the best of our knowledge, all seven previously reported cases of KD associated with HT occurred in females between the ages of 17 and 30 [1-4]. Three of these patients were diagnosed with HT before an episode of KD, whereas four patients were diagnosed with concurrent HT and KD.…”
mentioning
confidence: 99%
“…Kikuchi disease (KD), also known as histiocytic necrotizing lymphadenopathy, is a rare, benign condition usually characterized by cervical lymphadenopathy and fever [1]. The etiology of KD remains controversial, but autoimmune disorders including systemic lupus erythematous, tend to develop before, simultaneously, or after an episode of KD [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation